Validation of the Japanese version of the Body Image Scale for bladder cancer patients - Miho Sato; Takahiro Osawa; Takashige Abe; Michitaka Honda; Madoka Higuchi; Shuhei Yamada; Jun Furumido; Hiroshi Kikuchi; Ryuji Matsumoto; Yasuyuki Sato; Yoshihiro Sasaki; Toru Harabayashi; et al. (Scientific Reports, 2022)
Abstract The Body Image Scale (BIS) is a 10-item tool that measures the body images of cancer patients. This study aims to validate the Japanese version of the BIS for bladder cancer patients. A multicenter cross-sectional survey was used to identify the participants, which included Japanese bladder cancer patients. The percentage of missing responses, internal consistency, and known-group validity were evaluated. The correlations between the BIS and two HRQOL instruments (the Bladder Cancer Index and the SF-12) were assessed to determine convergent validity. Among 397 patients, 221 patients were treated by transurethral resection of bladder tumor (TURBT) endoscopically, 49 patients underwent cystectomy with neobladder, and 127 patients underwent cystectomy involving stoma. The percentage of missing responses in the BIS ranged from 8.1 to 15.6%. Cronbach's α coefficient was 0.924. Higher BIS scores indicate negative body image, and the median BIS score for patients with native bladders after TURBT (0.5) was significantly lower than those of the patients with neobladder (4.0) and stoma formation (7.0), which indicated the discriminatory ability of the BIS. Each domain of the Bladder Cancer Index and the role summary score of the SF-12 correlated to the BIS scores, which confirmed the convergent validity. A range of BIS scores were identified among patients who reported similar physical summary scores and mental summary scores of the SF-12. This study confirmed the reliability and validity of the Japanese version of the BIS for bladder cancer patients.